Hierarchical planning and reasoning about partially ordered plans—From theory to practice. Issue 4 (8th December 2022) - Bercher, Pascal
Abstract: This invited paper (part of the New Faculty Highlights Invited Speaker Program of AAAI'21 * ) surveys my work done until today. The reviewed work focuses on hierarchical task network (HTN) planning as well as on partial order causal link (POCL) planning. Lines of research include theoretical investigations (mostly computational complexity analyses), heuristic search, as well as the practical application of the technology for planning‐based assistants, which support a human user in carrying out various tasks.